Isolating elusive 'Al(μ-O)M' intermediates in CO2 reduction by bimetallic Al–M complexes (M = Zn, Mg). Issue 72 (23rd August 2022) - Evans, Matthew J.; Iliffe, George H.; Neale, Samuel E.; McMullin, Claire L.; Fulton, J. Robin; Anker, Mathew D.; Coles, Martyn P.
Abstract : We confirm that the μ-oxo species (NON Dipp )Al(μ-O)M (BDI Mes ) are viable intermediates in the conversion of CO2 to carbonate promoted by bimetallic Al–Mg and Al–Zn compounds. Abstract : The reaction of compounds containing Al–Mg and Al–Zn bonds with N2 O enabled isolation of the corresponding Al(μ-O)M complexes. Electronic structure analysis identified largely ionic Al–O and O–M bonds, featuring an anionic μ-oxo centre. Reaction with CO2 confirmed that these species correspond to the proposed intermediates in the formation of μ-carbonate compounds.